(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
In this article we address a problem raised by the adverb apenas: under certain circumstances it behaves as a negative polarity item, while in other cases it acts as a positive polarity element. After dividing the two interpretations and showing how some sentences can be ambiguous between two uses, we propose that apenas is a polarity item that does not lexically specify its orientation, but obtains an orientation from the syntactic context. Its appearance as a positive and negative item follows from the fact that in some contexts its syntactic configuration or semantic interpretation disallow one of the two polarities.